ANALISIS PETROFISIKA UNTUK MENENTUKAN OIL-WATER CONTACT PADA FORMASI TALANGAKAR, LAPANGAN “FBT”, CEKUNGAN SUMATRA SELATAN - Febrina Bunga Tarigan; Ordas Dewanto; Karyanto Karyanto; Rahmat Catur Wibowo; Andika Widyasari (Engineering Faculty Universitas Lampung, 2019)
In conducting petrophysics analysis, there are many methods on each property. Therefore, it is necessary to determine the exact method on each petrophysical property suitable for application in the field of research in order to avoid irregularities at the time of interpretation. The petrophysical property consists of volume shale, porosity, water saturation, etc. This research used six well data named FBT01, FBT02, FBT03, FBT04, FBT05, and FBT06 and also assisted with core data contained in FBT03. Core data used as a reference in petrophysical analysis because it was considered to have represented or closed to the actual reservoir conditions in the field. The area in this research was in Talangakar Formation,